1990
DOI: 10.1203/00006450-199003000-00002
|View full text |Cite
|
Sign up to set email alerts
|

LH Measurements by in Vitro Bioassay and a Highly Sensitive Immunofluorometric Assay Improve the Distinction between Boys with Constitutional Delay of Puberty and Hypogonadotropic Hypogonadism

Abstract: ABSTRACT. The basal and gonadotropin-releasing hormone (GnRH) stimulated levels of LH were measured in 21 boys with delayed puberty using conventional RIA, mouse interstitial cell in vitro bioassay (B-LH), and a highly sensitive immunofluorometric method (F-LH). On the basis of subsequent clinical follow-up, the subjects were diagnosed as idiopathic constitutional delay of puberty (CD, n = 13) or hypogonadotropic hypogonadism (HH, n = 8). The basal RIA LH levels were similar in the two diagnostic groups (HH, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The current study also showed than NB present significantly higher responses to GnRH than HH men in all parameters evaluated. These findings agree with previous studies that depict statistical differences between individuals with HH and teenagers with CDGP [3, 4, 24]. In the present study it becomes evident that these differences are also seen when HH men are compared to a younger group.…”
Section: Discussionsupporting
confidence: 83%
“…The current study also showed than NB present significantly higher responses to GnRH than HH men in all parameters evaluated. These findings agree with previous studies that depict statistical differences between individuals with HH and teenagers with CDGP [3, 4, 24]. In the present study it becomes evident that these differences are also seen when HH men are compared to a younger group.…”
Section: Discussionsupporting
confidence: 83%
“…It is therefore most important to design a cost-effective strategy for male DP. Many testing protocols have been investigated to address this issue, such as nocturnal sampling for LH (1,14), urinary gonadotropin measurement (15,16), plasma LH measurement by a highly sensitive immunofluorometric assay (17), GnRH agonist (GnRHa) stimulation test (18 -21) or a human chorionic gonadotropin (hCG) test (22 -26). So far no consensus has emerged about a single, reliable and easy test with acceptable sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…In the present case, LH immunoassays using various antibodies gave different results. Ultrasensitive immunoassays for LH (1,2), based on the sandwich technique and the use of monoclonal antibodies, have revealed some interesting aspects. The risk that monoclonal antibodies may be too specific has been pointed out (4), especially in cases where the protein or glycoprotein, like LH, is clearly microheterogeneous.…”
Section: Discussionmentioning
confidence: 99%